VEGAN SLOW COOKER - Sidey, Saskia (London : Hamlyn, 2021)
Perfect for busy lifestyles, these recipes will revolutionise your meal planning, meaning you can indulge in nutritious, comforting vegan dishes every night of the week with little to no effort. With dishes for breakfast, snacks, mains and sweet treats, this is simple food that the whole family can share and enjoy together. Recipes include: Seedy banana breakfast loaf, Tofu shakshuka, Satay cauliflower, Pulled jackfruit burgers, Mac n-no-cheese, Sweet potato shepherd's pie, Chocolate lava slab and Lemon blueberry drizzle
t Sweet treats.
Includes index
"Over 70 delicious recipes for stress-free meals" -- Cover
Keywords: Vegan cookery; Electric cooking, Slow; Cookbooks